Analisis Tingkat Kesehatan Keuangan Berdasarkan Keputusan Menteri BUMN Nomor Kep 100/Mbu/2002: Studi Kasus pada PT Pos Indonesia (Persero) Periode 2019-2022 - Hanny Maharani; Bonti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research is motivated by PT Pos Indonesia (Persero)'s plan to conduct an Initial Public Offering (IPO) in2025. The purpose of this study is to determine the level of financial health at State-Owned Enterprises, namelyPT Pos Indonesia (Persero) for the 2019-2022 period which will privatize in 2025. The research method usedis a quantitative method with a descriptive approach that refers to the Decree of the Minister of BUMN NumberKEP-100/MBU/2002 using eight financial ratios, namely Return on Equity, Return on Investment, Cash Ratio,Current Ratio, Collection Periods, Inventory Turn Over, Total Asset Turn Over and Ratio of Total Own Capitalto Total Assets. The research data source uses secondary data with data collection methods throughobservation, interviews, and literature studies. The results of this study indicate that the financial health levelof PT Pos Indonesia (Persero) in 2019 obtained the “Less Healthy” category with the predicate “BBB”, in 2020obtained the “Healthy” category with the predicate “A”, in 2021 obtained the “Healthy” category with thepredicate “A”, and in 2022 obtained the “Healthy” category with the predicate “A”